Plant Species with Antimicrobial Effects and the Importance of a Standardization of Protocols for Antimicrobial Agents - Nagpal, Kajal; Rani, Nidhi; Sharma, Prerna; Verma, Inderjeet; Dubey, Abhilasha; Handa, Uditi; Kansal, Vanshika; Dhankhar, Sanchit (Current Traditional Medicine, 2025)
In modern times, microbial resistance is a global threat to health and development. The misuse and inappropriate use of antimicrobials is the main cause of developing drug-resistant pathogens. It requires multiple areas in direction to attain sustainable advance goals. As a result of microbial resistance, the necessity for costly medications and expenses are obstructed worldwide. Due to rising attention in the research of new antimicrobial medicaments from a variety of natural or synthetic sources to fight microbial resistance. Thus, natural antimicrobial agents have been used to a great extent nowadays because plant-derived antimicrobial agents are considered to be safer alternatives for health as compared to those synthetic antimicrobial agents. Overall, the active ingredients, water, essential oils, and ethanolic extracts from selected plants and the mixture of a variety of these natural extracts have been used for centuries, because they possess antimicrobial activity which inhibits the growth of microbes. Natural plants as an antimicrobial agent, like extracts of Curcuma longa L., Piper nigrum L., Vachellia leucophloea, Eclipta prostrata, Ocimum sanctum L., Terminalia arjuna, Manihot esculenta Crantz, Lawsonia inermis L., Zingiber officinale Roscoe, Camellia sinensis (L.) Kuntze, Coriandrum sativum L., Carica papaya L., Cinnamomum tamala, and many others have been preferred and used for ages because they are easily available worldwide. They are usually of low cost and have little or no side effects. Several antimicrobial screening approaches like the disk-diffusion method, well diffusion method, micro broth dilution assay, sterile disk method, and agar diffusion method are generally cast off for measurement of reproducibility and standardization of these antimicrobial agents. This review article is a comprehensive description of natural plants like Coriandrum sativum L., Carica papaya L., Cinnamomum tamala, etc., containing those extracts used as antimicrobial agents listed, and numerous in vitro antimicrobial susceptibility testing methods are reported. These identified plant species and antimicrobial screening techniques hold the potential for formulating these plants into antimicrobial drugs, warranting further study and exploration in the field of medicine.
Keywords: antimicrobial screening